Dalle sfide interculturali, al"romanzo", al progetto socio educativo integrato - Anna Aluffi Pentini (Social Work and Society)
Intercultural challenge,"tale" and social educational strategy, Rome, November 2006: Police and Teachers deal differently with a little group of travellers. The analysis of this recent episode shows that intercultural issues are the basis of the educational commitment of the teachers but also of the prejudice of police and other people looking from outside to the relationship between teachers and travellers. The paradox of a double ethic concerning travellers needs to be deconstructed by the antiracist approach based on children rights. At the same time educational intervention cannot deal efficiently with emergency situations concerning children without cooperation with social work. The article underlines the role of democratic educational institutions in the developing appropriated strategies in dealing with complexes social issues which are not just to be"culturalised".